Pengaruh tata kelola perusahaan, kualitas audit, dan konservatisme terhadap persyaratan agunan pinjaman - Rani Puspa; Leni Triana; Rina Nopianti; Prastika Suwandi Tjeng (Jurnal Ekonomi Modernisasi, 2021)
Debtors and creditors have equal access to information about default risks in competitive credit markets. Loan collateral is less important in credit decision-making in these circumstances. However, in emerging credit markets such as Indonesia, where debtors and creditors do not have equal information about a firm's prospects, the use of collateral to mitigate default risk has become common practice. Despite the strong theoretical framework for the use of collateral to secure creditors from credit risk, some Indonesian firms are exempt from providing collateral for bank debts. This study looks at how the independence of the Board of Commissioners, governance committees, audit quality, and conservatism affect the likelihood of using debt collateral. Around 785 firms listed on the Indonesia Stock Exchange were collected using Slovin's formula, during the sample period of 2017-2020. According to logistic regression analysis, firms with a more independent Board of Commissioners, a separate governance committee, Big 4 auditors, and conservative accounting policies are less likely to provide loan collateral